Effect of antenatal detection of small-for-gestational-age newborns in a risk stratified retrospective cohort - Kajdy, Anna (PLoS One, 2019)
OBJECTIVE: Small-for-gestational-age (SGA) are neonates born with birth weight below the 10(th) centile for a given week of pregnancy. It is a risk factor of perinatal and neonatal morbidity and mortality. There is an ongoing debate whether prenatal detection of SGA neonates is good predictor of perinatal outcome especially in low risk populations. Our primary aim was to compare the odds ratios for unfavorable outcome in a risk stratified cohort of SGA neonates in regard to prenatal detection status. METHODS: This is a retrospective cohort study analysing the effect of prenatal detection on perinatal outcome. This cohort has been divided into a predefined low-risk and high-risk population. Electronic records of 39,032 singleton deliveries from 2010 through 2016 were analysed. SGA was defined as newborn weight below the 10(th) percentile on the Fenton growth chart. Detected SGA (dSGA) neonates were those that were admitted for delivery with a prenatal ultrasound diagnosis of abnormal growth. Undetected SGA (uSGA) were neonates that were found to be below the 10(th) percentile after birth. Perinatal and neonatal outcome was compared. RESULTS: The detection rate in high-risk pregnancies was almost 45.7% versus low risk where it amounted to 18.9%. In both the high-risk and low-risk populations there was a significantly higher risk of composite mortality for undetected SGA compared to approporiate-for-gestational-age (AGA) (OR 7.95 CI 4.76–13.29; OR 14.4 CI 4.99–41.45 respectively). The odds for the composite neonatal outcome were significantly higher for dSGA and uSGA than for AGA in all the studied populations except for the uSGA in high risk population (OR 1.57 CI 0.97–3.53). Importantly, there was not a single case of intrauterine fetal death among detected SGA, in the low risk group. CONCLUSIONS: Prenatal detection of SGA status is related to perinatal outcomes, especially mortality. Therefore, assessment of SGA status even in low-risk pregnancies could help predict potential perinatal and neonatal complications.